Dialogisme et spécificités du discours enseignant face à la scolarisation des enfants gitans - Nathalie Auger; Sophie Dufour (Recherches en didactique des langues et des cultures)
We have collected data in in a school exclusively hosting gypsy children and analyzed teaching discourse in a classroom. The class sessions studied refer to many previous discourses that we were able to record during an ethnographic survey that we conducted previously. These teachers’ discourses relate to the following subjects: absenteeism, languages and cultures in the classroom, subjects which are closely correlated with the schooling of gypsy children. The notion of dialogism has allowed us to understand, in action, the repercussions of absenteeism on class practices and led us to develop different didactic considerations.